PENGARUH METODE LEARNING START WITH A QUESTION (LSQ) TERHADAP KETERAMPILAN BERBICARA SISWA KELAS V SEKOLAH DASAR DALAM MENGAJUKAN DAN MENANGGAPI PERTANYAAN - Adinda; Sulfasyah; Rosmini Madeamin (STKIP Subang, 2025)
This study aims to determine the effect of the Learning Starts With A Question (LSQ) learning method on students’ speaking skills, specifically in the aspect of asking and responding to questions, in Grade V at SD Negeri Minasa Upa, Makassar City. This research is a Pre-Experimental Design and belongs to the quantitative research type. The sample consisted of 30 students. Data collection techniques included learning outcome tests and observation sheets. The data analysis techniques used were descriptive statistical analysis and a T-Test. The results showed that students' speaking skills, especially in asking and responding to questions, before the implementation of the Learning Starts With A Question (LSQ) method had a pretest average score of 64. Meanwhile, the posttest showed an improvement with an average score of 88.67. The T-Test analysis result on the effect of the Learning Starts With A Question (LSQ) method on students’ speaking skills in asking and responding to questions showed a significance value of 0.001, which is lower than the predetermined alpha value of 0.05 (0.001 < 0.05). Based on these results, it can be concluded that the null hypothesis (Ho) is rejected and the alternative hypothesis (H1) is accepted, indicating that the use of the Learning Starts With A Question (LSQ) method has a significant effect on students’ speaking skills in asking and responding to questions in Grade V at SD Negeri Minasa Upa, Makassar City.